A normative analysis of subsidization of all-electric vehicles in Germany - Christiane Malina (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2019)
The German government undertook several supportive measures to increase market penetration of all-electric vehicles (AEVs), e.g. a purchase rebate of 4000 Euro. In this paper, the fiscal measures are analyzed from a normative perspective. First, none of the arguments of market failure could be found to validate government intervention. In a first-order approximation of damage cost savings, the reduced external effect through driving, due to the displacement of internal combustion engine vehicles through AEVs, was found to be 5 times lower than the expenditures through the subsidy. Adding climate cost savings, total lifetime savings from driving equal the subsidy. However, considering life-cycle impact and additional subsidies, the purchase rebate cannot be justified. Secondly, German industrial policy could also not serve to justify government intervention. The purchase subsidy does not directly qualify for the industrial policy argument and private investment in battery technology and the charging infrastructure is established and preferred. Finally, allocating the true costs to each transport mode and thus internalizing the external effects is suggested as the approach of first-choice. For vehicles it is suggested that certificates have to be held by fuel suppliers, who then pass the price for pollution on to the end user. This provides an efficient and effective market solution to mitigate climate change and pollution effects and can increase AEV market penetration, if this is socially beneficial.
Keywords: 330